Pengaruh kesamaan komunikator dan target dalam kualitas persuasi - Choirul Anam (HUMANITAS: Indonesian Psychological Journal, 2004)
Suggestion through advice, religious proselytizing and semon for others are omitted. This is not merely because the suggestion is not true, it is also signed that there is people is bilief crisis toward communicator. The problem is located in the relationship between communicatorand target, who accept the suggestion. Belief to some information is the beginning of attitude changes. Hence belief to the information atributes a persuasion quality. Communicator was not viewed by the target as individual that is apart from the target him/ her self, but also someone that has an association with the target. Cognitive approach described the target thinking toward who the comunicator is.The study is aimed at understanding wether there is influence of similar elements between the communicators and the target toward persuation quality. The similarities include gender, tribe, and religion. Those similarities common self identies, usually are depicted by communicator's name. Metodologic practically, whether the information given by the communicator has similar element with the target him/ her self is more believable than from the communicator haring no element with the target.Sheet that contains some information is give to 87 subjects. The are asked for giving sign to which information that nerds testing. Sixty two out of the subjects serve as experimental group, receive information sheet attributed with the name of the communicator. As the control, the other 25 subjects receive information from the communicator whose name is abscure. The result of this study shows that there is no significant defferences between the group (p 0. 144 > 0.05). This means the communicator and the target similarity does not significantly influence the belief in the information. While difference between information content quality, show very significant differences (p 0. 000 < 0.05). This means that the information content quality has the most influenciai in the information.